Carotid artery stenosis contralateral to acute tandem occlusion: an independent predictor of poor clinical outcome after mechanical thrombectomy with concomitant carotid artery stenting - Maus, Volker; Seker, Fatih; Möhlenbruch, Markus Alfred (Cerebrovascular diseases, 2018)
Background and Purpose: Cerebral ischemic strokes due to extra-/intracranial tandem occlusions (TO) of the anterior circulation are responsible for causing mechanical thrombectomy (MT). The impact of concomitant contralateral carotid stenosis (CCS) upon outcome remains unclear in this stroke subtype. Methods: Retrospective analysis of prospectively collected data of 4 international stroke centers between 2011 and 2017. One hundred ninety-seven consecutive patients with anterior TO were treated with MT and acute carotid artery stenting (CAS). Clinical (including demographics and National Institutes of Health Stroke Scale [NIHSS]), imaging (including angiographic evaluation of CCS) and procedural data were evaluated. Favorable clinical outcome was defined as modified Rankin Scale (mRS) ≤2 at 90 days. Results: In 186 out of 197 TO patients preinterventional CT angiography was available for analysis, thereof 49 patients (26%) presented with CCS. Median admission NIHSS and procedural timings did not differ between groups. Reperfusion was successful in 38 out of 49 patients (78%) vs. 113 out of 148 patients (76%) without CCS. In stark contrast, rate of favorable outcome at 90 days differed significantly between groups (22 vs. 44%; p < 0.05). The presence of CCS in TO was associated with an unfavorable clinical outcome independent of age and NIHSS in multivariate logistic regression (p < 0.05). Final infarct volume was significantly larger in CCS patients (100 ± 127 vs. 63 ± 77 cm3; p < 0.05). Neither all-cause mortality rates (25 vs. 17%) nor frequency of peri-interventional symptomatic intracranial hemorrhage differed between groups (7 vs. 6%). Conclusion: For patients with anterior TO undergoing MT with concomitant CAS the presence of CCS >50% is an independent predictor of poor clinical outcome. This most likely cause is due to poorer collateral flow to the affected tissue.